Study on the Implementation of the Green Hotel Concept at Grand Hyatt, Nusa Dua, Bali - Roro Listya Angela Naibaho; Raja Fadhilah Firdaus; Cindy Fariida Dwiandara (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study examines the implementation of the green hotel concept at Grand Hyatt Bali, a five-star luxury resort located in the Nusa Dua Tourism Area, Bali, Indonesia. The growing environmental challenges caused by tourism activities have encouraged the hospitality industry to adopt more sustainable and environmentally responsible practices, making the green hotel concept increasingly significant. This study aims to identify the extent to which Grand Hyatt Bali has implemented the eleven criteria of the ASEAN Green Hotel Standard and to determine areas that still require improvement. A descriptive qualitative method was employed, with primary data obtained through a purposive interview with the hotel's Environmental Officer and supported by secondary data from relevant literature and official documents. The findings reveal that Grand Hyatt Bali has fulfilled ten out of eleven ASEAN Green Hotel Standard criteria, demonstrating strong implementation across environmental policy, green product use, community collaboration, human resource development, solid waste management, energy efficiency, water efficiency and quality, air quality management, noise pollution control, and wastewater management. The one criterion that remains partially unfulfilled pertains to hazardous waste and chemical management, specifically the absence of clearly marked dedicated sorting facilities for hazardous waste in public areas. This study recommends that the hotel install clearly labeled hazardous waste collection points, strengthen guest education through campaign materials, and conduct regular monitoring to ensure proper waste segregation. Addressing this gap would enable Grand Hyatt Bali to achieve full compliance with the ASEAN Green Hotel Standard and further contribute to sustainable tourism development in Nusa Dua, Bali. Keywords: ASEAN Green Hotel Standard, Grand Hyatt Bali, Green Hotel, Nusa Dua, Sustainable Tourism.